2021
DOI: 10.1002/cssc.202101157
|View full text |Cite
|
Sign up to set email alerts
|

β‐Zeolite‐Assisted Lignin‐First Fractionation in a Flow‐Through Reactor**

Abstract: The valorization of lignin, one of the main constituents of lignocellulosic biomass, is essential for an economically feasible biorefinery. In the present work, a hydrogen-free one step catalytic fractionation of woody biomass using commercial -zeolite as catalyst in a flow-through reactor was carried out, leading to a maximum aromatic monomer yield of 20.5 wt.%. Birch, spruce and walnut shells were compared as lignocellulosic feedstocks. -zeolite acts as a bifunctional catalyst, which prevents lignin repoly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 53 publications
1
12
0
Order By: Relevance
“…This setup enables physical separation and recovery of the catalyst and carbohydrate-rich pulp, which is a challenge for batch RCF operation. 19,22,23,25,[55][56][57] To evaluate the fractionation efficiency and monomer yields through RCF with different types of feedstocks, we conducted FT-RCF reactions with methanol and 50 : 50 w/w methanol/water. Subsequently, the produced lignin oil and solid pulp residue were analyzed.…”
Section: Resultsmentioning
confidence: 99%
“…This setup enables physical separation and recovery of the catalyst and carbohydrate-rich pulp, which is a challenge for batch RCF operation. 19,22,23,25,[55][56][57] To evaluate the fractionation efficiency and monomer yields through RCF with different types of feedstocks, we conducted FT-RCF reactions with methanol and 50 : 50 w/w methanol/water. Subsequently, the produced lignin oil and solid pulp residue were analyzed.…”
Section: Resultsmentioning
confidence: 99%
“…So far, Beta zeolites with various metal active sites have been impressed with assisting in the preferential fractionation of biomass and facilitating catalytic conversion to platform chemicals. , Catalytic conversion reactions on Beta involve hydrotreating, isomerization, dehydration, alkylation as well as catalytic cracking and pyrolysis, etc. Each reaction is not discussed exhaustively in this review and can be easily found in other literature. Many notoriously highly reactive reactions can be carried out by functionalized Beta, such as sugar isomerization or epimerization, , and production of lactates from carbohydrates, ,, as well as in more domino cascade reactions like conversion of 5-hydroxymethylfurfural from glucose, and production of γ-valerolactone from furfural . This is not possible with other catalysts.…”
Section: Catalysis Of Intergrowth Zeolitementioning
confidence: 99%
“…Kramarenko and his co-workers suggested that bzeolite effectively cleaved the ether linkage, e.g., b-O-4 of lignin, and also helped to control the repolymerization of the active radical intermediates. 12 Deepa et al observed the production of aromatic monomers predominantly from the pyrolysis of dealkaline lignin using zeolites (H-USY, H-ZSM-5, H-BEA and H-MOR). 13 As per a study, Shen and his co-workers suggested that specic Si/Al ratios of zeolites signicantly affected the production of aromatic hydrocarbons.…”
Section: Introductionmentioning
confidence: 99%